Inclusive spectra of protons from the interaction of alpha particles with 29Mev energy with 27Al and 59Co - Ussabayeva, G.; Zholdybayev, T.K.; Sadykov, B.M.; Duisebayev, B.A.; Nassurlla М. (Recent Contributions to Physics, 2018)
New experimental double-differential and integral spectra of the (4He,xp) reactions are presented at the 29 MeV energy of incident ions 4He on the 27Al and 59Co nuclei which used as structural elements and elements of the target assembly of the projected hybrid nuclear installations (ADS). To measure the cross sections of the reactions, a standard dE-E method was used, where two parameters of the detected particle are recorded: specific ionization and total energy. The systematic error of the measured double-differential cross sections did not exceed 10%. The statistical error varied from 5% to 15%, depending on the energy range of the emitted protons and the angle of their detection. The theoretical analysis of the experimental data is carried out within the framework of the PRECO-2006 code, which is based on modern theoretical models of nuclear decay. The mechanisms of nuclear reactions that form them are determined. The obtained experimental results fill the missing values of the cross sections of the studied reactions and can be used in the development of new approaches to the theory of nuclear reactions, as well as in the construction of hybrid nuclear power plants and in nuclear medicine.